Sawek Bangket: Ritual Ecology, Pest Governance, and Social Cohesion in Sasak Agriculture - Yeni Maulida; Bambang Eka Saputra; Zidni Zidni; Hary Murcahyanto (Sumber Belajar Sejahtera, 2026)
Indigenous and local knowledge is increasingly recognized in sustainability research, yet agricultural rituals are still often treated as symbolic survivals rather than as institutions that organize environmental observation, collective action, and intergenerational learning. This study examines Sawek Bangket, a Sasak agricultural ritual practiced in Kelayu Jorong Village, East Lombok, Indonesia, and asks how its history, ritual sequence, and social-ecological functions are understood by local knowledge holders. A qualitative historical-ethnographic design was employed between January and March 2025. Data were generated through semi-structured interviews with 12 purposively selected traditional leaders, religious figures, ritual practitioners, senior farmers, and community elders, together with participant observation and documentation. The data were interpreted through historical source criticism and thematic analysis. The findings show that community memory locates the tradition before living memory, while a major pest outbreak in the early 1980s appears to have reactivated or intensified its contemporary practice. Sawek Bangket combines field inspection, ritual preparation, Islamic prayers, symbolic materials, and post-ritual cooperation. Its principal contribution is not demonstrable biological pest control; rather, it provides a culturally legitimate framework for noticing threats, coordinating farmers, reinforcing environmental responsibility, and transmitting local knowledge. The article conceptualizes Sawek Bangket as ritual ecology and as cultural infrastructure for pest governance and social cohesion. The findings support respectful knowledge co-production in which local ritual practices complement, but do not replace, scientifically validated integrated pest management.